Hibridación interespecífica de arroz (Oryza rufipogon G. x Oryza sativa L. ssp. japonica) para la obtención de segregantes F1 con potencial genético en el desarrollo de germoplasma mejorado - Arana Vera, Viviana Susana (2016)
VIII. SUMARY Because of the por genetic diversity of rice for the generation of new germplasm adapted to the ecological condititions in Ecuador, this research aims to generate segregating F1 rice with potential genetic for the development germoplasm from interspecific crosses of wild rice with japonica rice. Single crosses were made from a wild parental and four japónica rice. The segregating populations F1 were established under grehause conditions and following variables were assessed: vigor floweing vegetative cycle, tillers per plant , panicle per plant, panicle per plant, length and widch flag left, length and width of the second leaf, plant height, panicle lengeth, grains per panicle, sterilinPg, husking 100 grain weight, gran length, grain shape, presence of edge length. Data were analized sing nonparametric statistics with the comparation metheod of Kruskal-wallis P’The obtained results suggest that there is genetic compatibility between puyon and japonica rice genotypes because F1 seeds were obtained by simple hybridization and the segregating populations were fertile. Crossing the puyon rice genotype with japonica, vigorous plants were obtained. There reciprocal crosses between wild rice and japonica JP00-3 resulted in segregating thin grain, longer panicle and number of tillers per plant than their parents. Interspecific hybridization allows to select earlier F1 segregating with desirable agronomic chararteristics.